2010
DOI: 10.1016/j.tsf.2010.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of parameters of chemical spray pyrolysis technique to get n and p-type layers of SnS

Abstract: SnS thin films were prepared using automated chemical spray pyrolysis (CSP) technique. Single-phase, p-type, stoichiometric, SnS films with direct band gap of 1.33 eV and having very high absorption coefficient (N 10 5 /cm) were deposited at substrate temperature of 375°C. The role of substrate temperature in determining the optoelectronic and structural properties of SnS films was established and concentration ratios of anionic and cationic precursor solutions were optimized. n-type SnS samples were also prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
71
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(81 citation statements)
references
References 24 publications
(28 reference statements)
4
71
0
Order By: Relevance
“…[2,5,14,15] A second technique is physical vapor deposition from a SnS target such as thermal evaporation, [16][17][18] RF sputtering, [19] and electron beam evaporation. [20] The last method uses transport by chemical vapors such as chemical spray pyrolysis, [21][22][23] chemical vapor deposition (CVD), [6,[24][25][26][27] and atomic layer deposition (ALD). [28] Due to various oxidation states of tin (0, +2, and +4), traces of other phases (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,5,14,15] A second technique is physical vapor deposition from a SnS target such as thermal evaporation, [16][17][18] RF sputtering, [19] and electron beam evaporation. [20] The last method uses transport by chemical vapors such as chemical spray pyrolysis, [21][22][23] chemical vapor deposition (CVD), [6,[24][25][26][27] and atomic layer deposition (ALD). [28] Due to various oxidation states of tin (0, +2, and +4), traces of other phases (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For vapor-based deposition techniques such as chemical spray pyrolysis and thermal evaporation, this effect is attributed to the high vapor pressure of sulfur, which evaporates out from the deposited film. [21,31] Nonstoichiometric SnS caused by either Sn +2 vacancies [32,33] or excess tin atoms [6,20] contains deep acceptor states with an activation energy (E a ) in the range between 0.22 and 0.45 eV [6,20,[32][33][34][35][36] depending on the deposition technique. The deep acceptor states, which could act as carrier recombination catalysts, are expected to lower the solar energy conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…16 Sajeesh et al reported n-type SnS thin films obtained by chemical spray pyrolysis, but this result is probably due to a significant n-type Sn 2 S 3 impurity phase in the films. 17 One promising n-type substitutional dopant is antimony(III), Sb 3+ , due to the similarity of its ionic radius to Sn 2+ . Albers et al reported the use of Sb as a dopant that lowers the hole concentration of SnS to be less than 10 14 cm -3 .…”
Section: Introductionmentioning
confidence: 99%
“…SnS exhibits both p-and n-type conductivity depending on the concentration of tin [10]. It has the advantage that the constituent elements are abundant in nature and do not cause any health and environmental hazards.…”
Section: Introductionmentioning
confidence: 99%
“…Tin sulphide have been prepared using a variety of deposition techniques, such as spray pyrolysis [6,10,15,43], thermal evaporation [13,16,51,39], electronbeam evaporation [17], hot wall deposition [18], chemical bath deposition [19,55], successive ionic layer adsorption and reaction [20], RF sputtering [21], atomic layer deposition [22], chemical vapor deposition [23,45,46], electrochemical deposition [4,24,41,54] and sulphurization [25,26,55]. Among them, sulphurization is one of the simple method that can be used to prepare SnS films over large area deposition at low cost with well controlled composition and it has proved as a most promising method for producing high quality CIGS and CIS thin films for solar cell fabrication.…”
Section: Introductionmentioning
confidence: 99%